The Role of Games in Security Design - Harris, Milton; Raviv, Artur (Review of Financial Studies, 1995)
We contend that security design should be approached as a problem of game design. That is, contracts should specify the procedures that govern the behavior of contract participants in determining outcomes as well as the allocations resulting from those outcomes. We characterize optimal contracts in two nested classes: all contracts (including those that depend on the state) and state-independent contracts. We demonstrate that, in situations in which the dependence of contracts on the state is limited, contracts designed as games can improve the allocation of resources relative to nonstrategic allocation rules.